The comparative study on the influence of inorganic soil amendment on the growth and leaching analysis of the brassica family - Norsuhailizah, Sazali; Norazlianie, Sazali; Zawati, Harun; Anuar, Ismail; Junaidi, Afdhal; Widiastuti, Nurul; Fansuri, Hamzah; Gunawan, Triyanda; Hartanto, Djoko (Semarak Ilmu Publishing, 2024)
Research on the positive effects of inorganic soil amendments in the agricultural sector has been steadily increasing to demonstrate their impact on plant development and the reduction of leaching. In this study, kaolin, metakaolin, zeolite, and perlite, which operate as inorganic soil amendments, were mixed with soil to determine their effectiveness in promoting Brassica growth and reducing the leaching of nitrite and nitrate. Seven alternative treatments; control standard (SS), control low (SL), 3g kaolin (3gK), 3g metakaolin (3gM), 3g zeolite (3gz), 5g of zeolite (5gZ), and 5g of perlite (5gP), were chosen to assess their effectiveness in the growth and reducing leaching in Brassica family (mustard green and kale). All the experiments were conducted in a greenhouse. According to the statistical analysis one-way ANOVA by comparing the mean, zeolite amended soil showed a higher significance difference in mustard green and kale growth analysis at harvest 1 and harvest 2 compared to other treatments. Kaolin, metakaolin, and perlite also showed slightly greater significance differences in mustard green and kale growth compared to the standard and low NPK treatments. In the leaching investigation, kaolin, metakaolin, zeolite, and perlite exhibited the lowest concentration of nitrate and nitrate compared to both standard NPK and low NPK. As demonstrated by the findings, inorganic soil amendments show the potential to improve the growth of mustard green and kale which also reduces the concentration of nitrate and nitrite, especially when using zeolite.